Opioids with abuse-deterrent properties: A regulatory and technological overview - Haddox, DDS, MD, J. David (Journal of Opioid Management, 2017)
Three concurrent public health problems coexist in the United States: endemic nonmedical use/misuse of opioid analgesics, epidemic overdose fatalities involving opioid analgesics, and endemic chronic pain in adults. These intertwined issues comprise an opioid crisis that has spurred the development of formulations of opioids with abuse-deterrent properties and label claims (OADP). To reduce abuse and misuse of prescription opioids, the federal Food and Drug Administration (FDA) has issued a formal Guidance to drug developers that delineates four categories of testing to generate data sufficient for a description of a product's abuse-deterrent properties, along with associated claims, in its Full Prescribing Information (FPI). This article reviews the epidemiology of the crisis as background for the development of OADP, summarizes the FDA Guidance for Industry regarding abuse-deterrent technologies, and provides an overview of some technologies that are currently employed or are under study for incorporation into OADP. Such technologies include physical and chemical barriers to abuse, combined formulations of opioid agonists and antagonists, inclusion of aversive agents, use of delivery systems that deter abuse, development of new molecular entities and prodrugs, and formulation of products that include some combination of these approaches. Opioids employing these novel technologies are one part of a comprehensive intervention strategy that can deter abuse of prescription opioid analgesics without creating barriers to the safe use of prescription opioids. The maximal public health contribution of OADP will probably occur only when all opioids have FDA-recognized abuse-deterrent properties and label claims.